Pemikiran Islam Kontemporer Abdullah Saeed dan Implementasinya dalam Persoalan Murtad - Ach Musif (Universitas Islam Negeri Mataram, 2015)
Western media coverage on Islam and especially on terror attacks by Muslims has been exaggerated and pejorative. This stereotyping has portrayed Islam as problems. First, Islam is seen as sluggish in responding modernity and the advance of science and knowledge so it always lacks behind the West. Second, Islam is associated with extremism and terrorism which are incompatible with the West. Therefore, the emergence of rational thinking and cosmopolitan approach to Islam promoted by Muslim reformists, such as Abdullah Saeed, are very urgent to encounter such stereotype and discourse on Islam in the West. This article examines Saeed’s method called “progressive Islam”. By taking one example of conversion (murtād), this article elucidates how the method of ijtihād progressive is applied in one of the most controversial topics in Islamic law. This study shows that the law on murtād, as it was introduced by classical Muslim jurists, is now adopted by Muslim countries. However, such adoption does not have a sound ground on the Qur’anic texts and the Sunnah. DOI: http://dx.doi.org/10.20414/ujis.v19i1.1251